Upbringing, interpersonal difficulties and drug use - Veronica Guzmán-Ramirez; María Magdalena Alonso-Castillo; Nora Angélica Armendáriz-García; Bertha Alicia Alonso-Castillo; Manuel Antonio López-Cisneros; Brett Homero Cisneros-Zaleta (Escola de Enfermagem de Ribeirão Preto da Universidade de São Paulo, 2015)
Determining upbringing and interpersonal difficulties among those drug consumers and non consumers and identifying the relationship and effects of upbringing and interpersonal difficulties on drug consumption through a descriptive and correlative study using adolescents selected through cluster sampling. The study discovered that upbringing and interpersonal difficulties can predict having ever consumed alcohol and having consumed it within the last year. When a negative perception of upbringing exists, alcohol consumption exists; the greater the number of interpersonal difficulties, the greater the adolescents' alcohol consumption.